Financing Chinese investments in the Brazilian electricity infrastructure: concerns on international subsidies. - Germanò, Marco André; Kroetz, Maria Eugênia (Seminário Pesquisar China Contemporânea, 2021)
The exact definition of what a subsidy is has always been a controversial matter (GERASIMCHUK, 2014). Following the political and economic rise of the People’s Republic of China, a non-market economy for many countries (O'CONNOR, 2011; HALEY & HALEY, 2013), the issue has spurred new global tensions. Feelings of distrust and lack of reciprocity regarding the Asian country, arguably, have impelled other nations, most notably the United States, to question international economic rules, including the standard trade and foreign direct investment (FDI) regimes under the World Trade Organization (WTO) and the Organization of Economic Cooperation and Development (OCDE) (CROCHET & HEDGE, 2020). The present research contributes to the academic literature that discusses the issue of subsidy rules and financing ease at the international level by looking at the case of Chinese direct investments in Brazil’s electricity sector. It aims to answer two main questions: whether the Chinese State-Owned Enterprises’ (SOEs) regulatory structure guarantees them facilitated access to capital and, in case of a positive response, whether this economic ease could be an advantage over other global players, distorting the competitivity of the Brazilian market. We look at the electricity matrix due to the noteworthy inflows of China’s FDI into the sector, which are in the verge of outcompeting traditional investors from North America and Europe. This research looks at the study of international subsidies, the governance structure of Chinese SOEs, Brazil’s regulatory framework, and the characteristics of Sino investments in Brazil’s energy matrix.